Study on the Development of Education: Contextual Secondary Education in Papua - Hamadi, Hans (Journal of Education and Vocational Research, 2017)
Utilizing knowledge of education to manage technology as modern human lifestyles and meet the demands of work and life is the subject of this study. While those living in the suburbs to meet the demands of education, utilizing information technology as a way of life will come to their rescue. They also still use the natural wealth of forests, mountains and oceans as a source of learning and life. In remote areas, technology and the demands of rapid change, are sluggish and does not make the technology as a necessity of life. They depend on nature to meet their educational knowledge as well as the necessities of life. How technology can be implemented and enjoyed on this earth without distinguishing its diversity. They utilize contextual nature as education and then institutionalized it in teaching. Every human being has the same rights and if in fact there is a gap it means that there is injustice. So there are things that need to be repaired. The knowledge and skills of human resources in the context of this study are defined as an entity of teachers. Human and organizational resources, which indeed underlies the base of organizational performance. There is a substantive difference between knowledge and skill. The concept of knowledge is more oriented to intelligence, intellect, and extensive mastery of knowledge and the narrowness of insight that one. This is a qualitative descriptive study based on the paradigm of post positivism. Qualitative research is still using the theories and concepts that are not tested as in positivism paradigm. The results of the study of literature are (1) The need for establishing educational institutions in each region are categorized as remote and isolated areas. (2) Closer direct services to remote and isolated areas then form the institution can be either natural school. (3) Adequate education that is modified and performed should remain principled and lead to economic value, efficiently utilize the environment without leaving the quality of education. Efforts to render these services is in line with Government Regulation No. 19 Year 2005 on National Education Standards, at the school level, which can be used as a referral to the rule above are: (1) education as a process of acculturation and empowerment. (2) Education in order to increase the nation’s competitiveness. (3) Education for development. (4) Education for affirmative action / serving disadvantaged communities. (5) The commitment to the policy of providing certain types of education.